Kebijakan Penyelenggara Pemilihan Umum Terkait Pemungutan Suara Ulang Pada Pemilu Legislatif Tahun 2014 - Dewi Haryanti (Jurnal Selat, 2014)
Legislative elections are elections to choose members of the DPR, DPD and DPRD. Elections of 2014 refers to the Law No. 8 of 2012 that the implementation of voting takes place on Wednesday, April 9, 2014. In each stage of the implementation of the election can not be separated from the existence of the phenomena observed and found to be studied. In the 2014 legislative elections this phenomenon to the attention of the author is the repeat voting. Of the 546,278 polling stations inside and outside the country, as many as 779 polling stations have to hold repeat polls including Tanjungpinang. As for the problem of this research is related to policy organizer re-election in voting in Tanjungpinang. The research method used is descriptive analytical research through a qualitative approach. Sources of data obtained through primary data is the main data obtained directly from informants through interviews with commissioners and staff KPU secretariat Tanjungpinang and secondary data is data obtained from literature books, legislation, internet and other scientific work. From the research it can be concluded that the author Tanjungpinang KPU vote again at the polling place that TPS 275/36 by reason of ballots confused. In the implementation of revoting, Election Commission Tanjungpinang based on the electoral law, regulations and the Commission Circular. In principle the setting because of the re-voting ballots are not dealt with explicitly swapped in the laws or regulations of KPU. Technical implementation of the policy re-voting are set forth in Circular No. 275/KPU/IV/2014 Commission and the Commission Circular No. 306/KPU/IV/2014. Keywords: Policy, General Elections, Legislative and Voting Re-